Gender Equality: Do I care? - M. K., Anis-Farahwahida; Ab Raji, Nurul Atiqah (Opción, 2019)
The core objective of this study is to examine the future counselor’s awareness of the importance of gender equality by cogitate on gender elements during counseling sessions via the questionnaire has been divided into three sections. As a result, there was a statistical significance of the effect of age and experiences on future counselor’s gender equality awareness and its importance. In conclusion, the good understanding and high awareness of gender equality, the cultural institutions favoring males might themselves fade naturally with economic and social modernization so as to enable gender gaps to narrow and close later.